Dietary nitrate intake in well-trained athletes - Jonvik, K. L.; Wardenaar, F. C.; Nyakayiru, J.; Senden, J. M. G.; Van Loon, L. J. C.; Verdijk, L. B. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
BACKGROUND: Beetroot juice, as a carrier of dietary nitrate, has become a popular ergogenic supplement in athletes. However, we consume nitrate via many other foods and food groups in our diet. PURPOSE To assess dietary nitrate intake and identify the main food sources that contribute to daily nitrate intake in a large group of well-trained athletes. METHODS: 553 Dutch well-trained athletes (226 women and 327 men) completed multiple web-based 24-h dietary recalls and questionnaires within a 2-4 week period. We calculated daily nitrate intake following an assessment of the nitrate content of various foods and food groups. Gender differences were analyzed using independent t-tests. Correlations between energy, nitrate and vegetable intakes were analyzed using Pearson correlations. Results are reported as mean±SD. RESULTS: Habitual nitrate intake was 132±87 mg/d (range 19-525 mg/d). Daily nitrate intake tended to be higher in women vs men (141±90 vs 127±84 mg/d; P=0.061). Despite substantially lower total energy intake in women vs men (9.0±2.4 vs 11.5±3.2 MJ/d, P<0.001), total vegetable intake was higher in women vs men (186±142 vs 136±101 g/d; P<0.001). When corrected for energy intake, nitrate intake was substantially higher in women vs men (15.7±9.3 vs 11.3±7.2 mg/MJ; P<0.001). A positive correlation was observed between daily energy intake and nitrate intake (r=0.27, P<0.001), and an even stronger correlation between daily vegetable intake and nitrate intake (r=0.75, P<0.001). In accordance, the majority of habitual nitrate intake was consumed through ingestion of vegetables and fruit (including potatoes), accounting for 77% of total nitrate intake in women and 71% in men. Lettuce and spinach were the products contributing most. Only 2% of the athletes (10 out of 553) reached a daily nitrate intake above the standard supplement dose of 400 mg. CONCLUSIONS: Well-trained athletes have an average daily nitrate intake of 132 mg (19-525 mg). Dietary nitrate intake is significantly correlated with total energy intake and largely determined by the amount of vegetables consumed.